On Preradical of Semimodules (Baghdad Science Journal, 2018)
In this paper we study the notion of preradical on some subcategories of the category of semimodules and homomorphisms of semimodules.Since some of the known preradicals on modules fail to satisfy the conditions of preradicals, if the category of modules was extended to semimodules, it is necessary to investigate some subcategories of semimodules, like the category of subtractive semimodules with homomorphisms and the category of subtractive semimodules with ҽҟ-regular homomorphisms.